Flora vascular de la provincia de Santa Fe - PENSIERO, José Francisco (UNIVERSIDAD NACIONAL DEL LITORAL, 2005)
Colaboradores: LUCHETTI, Ana María; EXNER, Eliana; KERN, Verónica; BRNICH, Esteban; OAKLEY, Luis; PRADO, Darién; LEWIS, Juan Pablo